Disparities and distrust: the implications of psychological processes for understanding racial disparities in health and health care. - Dovidio, John F; Penner, Louis A; Albrecht, Terrance L; Norton, Wynne E; Gaertner, Samuel L; Shelton, J Nicole (Social science & medicine (1982), 2008)
This paper explores the role of racial bias toward Blacks in interracial relations, and in racial disparities in health care in the United States. Our analyses of these issues focuses primarily on studies of prejudice published in the past 10 years and on health disparity research published since the report of the US Institute of Medicine (IOM) Panel on Racial and Ethnic Disparities in Health Care in 2003. Recent social psychological research reveals that racial biases occur implicitly, without intention or awareness, as well as explicitly, and these implicit biases have implications for understanding how interracial interactions frequently produce mistrust. We further illustrate how this perspective can illuminate and integrate findings from research on disparities and biases in health care, addressing the orientations of both providers and patients. We conclude by considering future directions for research and intervention.
Keywords: African Americans; Health Services Accessibility; Health Status Disparities; Healthcare Disparities; Humans; Sociology, Medical; Trust